Simultaneous Preconcentration of Cadmium(II) and Lead(II) in Water Samples Using Resin Amberlite XAD-2 Functionalized with Nitroso R Salt and Determination with Atomic Absorption Spectrometry - Tajodini, Nilofar; Moghimi, Ali (Asian Journal of Chemistry, 2010)
A preconcentration/separation procedure is presented for the solid phase extraction of trace cadmium and lead ions in environmental samples on Amberlite XAD-2 functionalized with nitroso R salt resin, prior to cadmium and lead determinations by atomic absorption spectrometry. The preconcentration procedure was optimized by using model solutions containing cadmium and lead ions. The influence of pH on the model solutions, amounts of, eluent type and volume, etc. were investigated. The effects of the matrix constituents of the samples were also examined. Separation of cadmium and lead from real samples was achieved quantitatively. The procedure presented was checked with the analysis of standard reference materials (IAEA-336 Lichen and SRM 1515 Apple leaves). The preconcentration procedure was applied for the lead and cadmium contents of the natural water samples, with satisfactory results (recoveries > 95 %, relative standard deviations < 7 %).